The Effect of Perioperative Topical Ketorolac 0.5% on Macular Thickness after Uneventful Phacoemulsification. (23rd November 2017) - Dal, Derya; Sarac, Ozge; Toklu, Yasin; Kocak Altintas, Ayse Gul; Cakmak, Hasan Basri; Damar Gungor, Elif; Simsek, Saban
Abstract : Background . To evaluate the effects of topical 0.5% ketorolac treatment combined with topical steroids on macular thickness in cases who had uneventful phacoemulsification surgery. Methods . 58 eyes of 58 consecutive cases were included. The mean foveal thickness (MFT), parafoveal thickness (ParaFT), and perifoveal thickness (PeriFT) measurements were performed with optical coherence tomography (RTVue-100, Optovue, Fremont, CA, USA) preoperatively and at postoperative 1 week, 1 month, and 2 months. All cases received topical 0.1% dexamethasone postoperatively. Randomly selected cases additionally received topical 0.5% ketorolac, which started 2 days prior to surgery. Cases who received both topical steroids and ketorolac formed group 1 and subjects who received only topical steroids formed group 2. Results . The increase in mean MFT at the 1st week, 1st month, and 2nd months after surgery in group 1 was significantly lower than group 2 (P = 0.008, P ≤ 0.001, and P ≤ 0.001, resp.). In group 1, the increase in mean ParaFT and PeriFT was significantly lower than group 2 at the 1st and 2nd months of the surgery (P < 0.05 for all variables). Conclusions . Topical ketorolac combined with steroids is highly efficacious in order to prevent increment in thickness on each part of the macula even after an uneventful phacoemulsification surgery comparing to steroid monotheraphy.